2022
DOI: 10.3389/fgene.2022.1007046
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral phenotype of Kabuki syndrome: Anxiety is a common feature

Abstract: Kabuki syndrome (KS) is a Mendelian Disorder of the Epigenetic Machinery (MDEM) caused by loss of function variants in either of two genes involved in the regulation of histone methylation, KMT2D (34–76%) or KDM6A (9–13%). Previously, representative neurobehavioral deficits of KS were recapitulated in a mouse model, emphasizing the role of KMT2D in brain development, specifically in ongoing hippocampal neurogenesis in the granule cell layer of the dentate gyrus. Interestingly, anxiety, a phenotype that has a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…There was also no significant difference between participants with KS1 (average of 64.7) and participants with KS2 (average of 75.5). It has been previously reported that anxiety is specific neurobehavioral feature of individuals with KS (Kalinousky et al, 2022). When comparing the 56 participant's SCARED/GAS-ID anxiety scores with their sleep scores, we found that sleep issues and anxiety were positively correlated (r = 0.40, p = 0.002).…”
Section: Participantsmentioning
confidence: 57%
“…There was also no significant difference between participants with KS1 (average of 64.7) and participants with KS2 (average of 75.5). It has been previously reported that anxiety is specific neurobehavioral feature of individuals with KS (Kalinousky et al, 2022). When comparing the 56 participant's SCARED/GAS-ID anxiety scores with their sleep scores, we found that sleep issues and anxiety were positively correlated (r = 0.40, p = 0.002).…”
Section: Participantsmentioning
confidence: 57%
“…KS1 is a neurodevelopmental disorder caused by mutations in the gene encoding KMT2D , a member of the same family of histone lysine methyltransferases as KMT2A , which is disrupted in WSS. The KMT2 family of proteins methylates H3K4, and pathogenic variants in KMT2D have already been shown to cause elevated risks of anxiety compared to sibling controls in KS (Kalinousky et al, 2022). Cross‐MDEM comparisons will elucidate shared mechanisms for developmental trajectories of select psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, pathogenic variants in KDM5B , a H3K4 demethylase, has been similarly linked to intellectual impairment and high risk of ASD (Tseng et al, 2022), with animal models of the disorder showing ASD‐like behaviors (repetitive behaviors, reduced socialization and vocalization, and learning deficits) (El Hayek et al, 2020). However, those with Kabuki syndrome (KS), a genetic disorder most commonly caused by loss of function variants in KMT2D —another related member of the KMT2 methyltransferases involved in methylation of H3K4—present with a relative strength in interpersonal and social communication skills despite higher risk for anxiety (Kalinousky et al, 2022; Mervis et al, 2005; Schrander‐Stumpel et al, 2005). At present, the specific mechanism by which chromatin regulatory systems impact neurogenesis of specific neural substrates involved in social cognition, communication skills and behavior regulation remains unknown.…”
Section: Introductionmentioning
confidence: 99%